Economic crisis prediction due to pandemic outbreak using machine learning - Ahmed, Tanvir; Hasan, MD. Nahid; Ashik, Md.; Hasan, Md. Jahid (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.